Metabesity: pathogenetic bases and predictive capabilities. A review - Mekan R. Orazov; Viktor E. Radzinsky; Marina B. Khamoshina; Evgeny D. Dolgov; Irina A. Mullina; Yulia S. Artemenko; Valentina A. Ryabova (IP Berlin A.V., 2023)
One of the most pressing problems of our time is obesity, recognized by the WHO as a pandemic of the XXI century. It is important to remember that obesity is a full-fledged nosological entity, but many women think that obesity is just a problem of beauty and aesthetics. It is important to note that this nosology has a number of serious consequences, starting with the development of cardiovascular disease and ending with cancer. However, the "problem in the problem" is the so-called "metabesity" - a new term that reflects a number of diseases, the pathogenesis of which is based on the metabolic syndrome. Obesity, metabolic syndrome and metabesity seem to be different concepts, but the absolute identity of the pathogenetic basis characterizes them as successive stages of one global process. In this regard, it is necessary to highlight the key mechanisms of the development of the described disorders and to consider the concept of clinical management of patients in this cohort.